Clinical guidelines for sclerotherapy: implementation in actual practice - S. M. Markin; V. Yu. Bogachev; S. V. Grishin; P. F. Kravtsov; K. V. Mazayshvili (Амбулаторная хирургия)
Introduction. The simplicity of the sclerotherapy procedure, its high efficiency and low cost along with the possibility of performing the procedure on an outpatient basis stimulate the widespread use of the method.Objective of the study. Examine the current state of actual clinical practice regarding the treatment of patients with varicose veins using the sclerotherapy procedure.Materials and methods. An anonymous survey of 162 doctors, members of the professional community of specialists engaged in the treatment of venous diseases was performed. It comprised 15 questions concerning the features of the sclerotherapy procedure and following up of the patients.Results and discussion. The lack of clear-cut standardization for sclerotherapy in the regulatory documents contributes to the significant heterogeneity in the approaches of specialists to the performance of the procedure. The views on the use of sclerotherapy to remove perineal varicose veins (routinely performed only by 25.3% of physicians) and the upper extremity veins (less than 4%) turned out to be controversial. There were significant differences in the therapeutic approaches to the administration of anticoagulants by the patients (refusal in the procedure – 26.3% of respondents, discontinuation of drugs during sclerotherapy – 7.5%). Approximately a third of the respondents regularly exceed recommended 10 ml-volume of foam per session, there is no consensus on the choice of the needle diameter, drug concentration even in the similar clinical situations. About half of them have experience in using glucose as the sclerosant, every third – in using a transcutaneous laser, 5.6% – in using the mechanochemical obliteration techniques that are not currently certified in the Russian Federation. The use of compression therapy after sclerotherapy is not standardized; the regulatory documents provide contradictory durations of its use, which is due to the weakness of clinical research data on this issue. Up to 99% of physicians observe pigmentation, 83.2% – development of secondary telangiectasias and 60.2% – superficial necrosis in their practice. These circumstances arouse legal suspicion in relation to this type of treatment and the legal vulnerability of physicians. At the same time, physicians need to be more informed about the current requirements for some issues.Conclusion. The current legislation regulating the practical aspects of the sclerotherapy considers it largely through the lens of medicine, ignoring a significant cosmetic component. It is necessary to work out the provisions describing the specifics of cosmetic manipulations performed by the phlebologists, and the need for more detailed familiarization with the regular updates of the guidelines.